2012
DOI: 10.1158/1078-0432.ccr-12-0160
|View full text |Cite
|
Sign up to set email alerts
|

MAX Mutations Cause Hereditary and Sporadic Pheochromocytoma and Paraganglioma

Abstract: Purpose: Pheochromocytomas (PCC) and paragangliomas (PGL) are genetically heterogeneous neural crest-derived neoplasms. Recently we identified germline mutations in a new tumor suppressor susceptibility gene, MAX (MYC-associated factor X), which predisposes carriers to PCC. How MAX mutations contribute to PCC/PGL and associated phenotypes remain unclear. This study aimed to examine the prevalence and associated phenotypic features of germline and somatic MAX mutations in PCC/PGL.Design: We sequenced MAX in 1,6… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
264
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 288 publications
(292 citation statements)
references
References 34 publications
21
264
0
6
Order By: Relevance
“…Furthermore, these genes explain w2% of all PCC/PGL cases in our series, independently of the age of onset, so only by increasing the number of pediatric cases analyzed, we should be able to confirm the absence of association of these four genes with young-age PCC/PGL development. On the other hand, the occurrence of one MAX case among pediatric probands is in agreement with its recently reported role as a PCC/PGL susceptibility gene (Burnichon et al 2012). This finding becomes more relevant when considering that the prevalence of MAX mutations (1.1% in our whole series) is quite similar to that reported for the latest identified PCC/PGL susceptibility genes (Welander et al 2011).…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, these genes explain w2% of all PCC/PGL cases in our series, independently of the age of onset, so only by increasing the number of pediatric cases analyzed, we should be able to confirm the absence of association of these four genes with young-age PCC/PGL development. On the other hand, the occurrence of one MAX case among pediatric probands is in agreement with its recently reported role as a PCC/PGL susceptibility gene (Burnichon et al 2012). This finding becomes more relevant when considering that the prevalence of MAX mutations (1.1% in our whole series) is quite similar to that reported for the latest identified PCC/PGL susceptibility genes (Welander et al 2011).…”
supporting
confidence: 92%
“…Before the discovery of these genes, 30-40% of PCC/PGL cases were thought to be hereditary with autosomal inheritance caused by germline mutations affecting one of six major susceptibility genes: RET, VHL, SDHB, SDHC, SDHD, and NF1 (Cascon et al 2009b, Mannelli et al 2009). Recent international collaborations, focused on establishing the involvement of the novel identified genes, suggested that overall they could explain an additional 6% of the negative-tested patients (Bayley et al 2010, Burnichon et al 2012. In addition to this high and heterogeneous genetic predisposition, there is a unknown percentage of familial cases (i.e.…”
mentioning
confidence: 99%
“…У 37% прослеживался семейный анамнез, и только 10% имели мета стазы. Средний возраст манифестации заболевания -32 года, но в 21% случаев -до 18 лет, что обязало включить мутации МАХ наряду с VHL и SDHB в панели генетического тестирования в педиатрической практике [48]. Для опухолей характерны преобладание секреции норметанефрина и нормальный (или незначительно повышенный) уровень метанефрина.…”
Section: Max (14q233)unclassified
“…MAX protein is a cofactor of the proto-oncogene MYC and is a key component of the MYC-MAX-MXD1 network that regulates cell proliferation and differentiation, exhibiting crosstalk with the mammalian target of rapamycin (mTOR) pathway. Burchinon et al [64] reported a multicentre series of 1,694 patients with PCCs/PGLs in whom MAX was sequenced. They ascertained that MAX germline mutations are present in 1.12% of cases of PCC/PGL in patients with no other known mutation.…”
Section: Genetic Mutations In Malignant Pheochromocytomas and Paraganmentioning
confidence: 99%
“…In contrast, patients with VHL demonstrated solitary increases in normetanephrine, whereas 70% of patients with an SDH mutation demonstrated additional or solitary increases in methoxytyramine (dopamine production). More recently, it was reported that PCCs/PGLs associated with MAX mutations are characterized by substantial increases in normetanephrine and may be associated with normal or minor increases in metanephrine [64].…”
Section: Genotype/mutation Correlationsmentioning
confidence: 99%